Valproate-induced hyperammonemic encephalopathy in a child without hepatic failure: A case report - Dudipala, Sai Chandar; Mandapuram, Prashanthi; Kumar, Chennadi Amith (Indian Journal of Case Reports, 2020)
Sodium valproate or valproic acid (VPA) is an effective antiepileptic drug that is commonly used for epilepsy in children because of its broad-spectrum activity. The use of VPA frequently results in elevated plasma levels of ammonia with or without raised transaminases. This condition usually happens when VPA with polypharmacy or underlying metabolic disorders like urea cycle defects. We are reporting a case of valproate-induced hyperammonemic encephalopathy in a child which is rare in children. Health professionals should be aware of this potential complication, and it is highly recommended to check ammonia levels in patients taking VPA who present with a change in mental status. If identified early, it can treat with appropriate measures and it can reversible.